Erosion of luting cements exposed to acidic buffer solutions - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2007)
The aim of this study was to evaluate acidic erosion of 7 luting cements. Erosion was evaluated via immersion in 0.1 M aqueous sodium lactate/lactic acid buffer (pH = 2.74 and 4.0, respectively). The rank order of cement loss was as follows: Phosphate Cement > Fuji I hand-mixed = Fuji I encapsulated > Ketac Cem > Calibra = Fuji Plus Variolink Ultra. Cement type, pH, and time had statistically significant effects. Water-based cements exhibited more erosion compared to resin-based cements, and the latter underwent hygroscopic expansion caused by water sorption.
Keywords: SOLUBILITY